Pretreatment of donor islets with papain improves allograft survival without systemic immunosuppression in mice. Issue 5 (2nd September 2016) - Kumano, Kenjiro; Nishinakamura, Hitomi; Mera, Toshiyuki; Itoh, Takeshi; Takahashi, Hiroyuki; Fujiwara, Toshiyoshi; Kodama, Shohta
ABSTRACT: Although current immunosuppression protocols improve the efficacy of clinical allogenic islet transplantation, T cell-mediated allorejection remains unresolved, and major histocompatibility complexes (MHCs) play a crucial role in this process. Papain, a cysteine protease, has the unique ability to cleave the extracellular domain of the MHC class I structure. We hypothesized that pretreatment of donor islets with papain would diminish the expression of MHC class I on islets, reducing allograft immunogenicity and contributing to prolongation of islet allograft survival. BALB/c islets pretreated with papain were transplanted into C57BL/6J mice as an acute allorejection model. Treatment with 1 mg/mL papain significantly prolonged islet allograft survival. In vitro, to determine the inhibitory effect on T cell-mediated alloreactions, we performed lymphocyte proliferation assays and mixed lymphocyte reactions. Host T cell activation against allogenic islet cells was remarkably suppressed by pretreatment of donor islet cells with 10 mg/mL papain. Flow cytometric analysis was also performed to investigate the effect of papain treatment on the expression of MHC class I on islets. One or 10 mg/mL papain treatment reduced MHC class I expression on the islet cell surface. Pretreatment of donor islets with papain suppresses MHC class I-mediated allograft rejection in mice and contributes to prolongation of islet allograft survival without administration of systemic immunosuppressants. These results suggest that pretreatment of human donor islets with papain may reduce the immunogenicity of the donor islets and minimize the dosage of systemic immunosuppressants required in a clinical setting.